OPTIMASI LAMA BLANCHING PENGOLAHAN SELAI KACANG TANAH METODE REGRESI KUADRATIK - Wirawan Wirawan; Wahyu Mushollaeni (BUANA SAINS, 2008)
The aims of this study were to elucidate the best time for blanching of peanut jams using quadratic regression, and the financial aspects. Six treatments of blanching time, i.e. 5, 10, 15, 20, 25 and 30 minutes were applied. Analytical factors were water content, texture, capability of performance, total of microbial and also hedonics i.e. texture, colors and flavors. Results of this study showed that the best time for blanching was 30 minute and this produced best quality of peanut jams